MULTIPLICATION AND in vitro ROOTING OF Campomanesia adamantium CAMB. - ROSSATO, MARIELI; SCHUMACHER, PEDRO VITOR; NETTO, ANTÔNIO PAULINO DA COSTA; DE SOUZA, GEICIANE CINTRA; DOS REIS, EDÉSIO FIALHO; STEIN, VANESSA CRISTINA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
The aim of this work was to evaluate the influence of growth regulators BAP, IBA, NAA and IAA in the propagation of Campomanesia adamantium CAMB. Nodal segments from seedlings maintained in vitro at the fourth subculture (subculture 40 to 40 days) were used. WPM culture medium supplemented with 30 g L-1 sucrose, 7 g L-1 agar and 0.9 mM PVP was used. For shoot induction, different concentrations (0; 0.25; 0.5; 1.0 and 2.0 mg L-1) of BAP were tested. For root induction, different concentrations (0.5; 1.0; 1.5 and 2.0 mg L-1) of IBA, NAA and IAA were used. The explants were maintained in growth room with light intensity of 43 μmol m-2 s-1 and a temperature of 25 ºC. We used a completely randomized design with 5 replicates (each replicate with three tubes). For shoot length, analysis of the experiment was conducted in a factorial 2x5 (two evironments and five concentrations). For the shoot variable, multiplication rate and leaves presented no significant difference, but the length shoot showed the highest average using 1.0 mg L-1 BAP when induced in the dark. Results for root number were not significant. The concentration indicated for shoot induction is 1.0 mg L-1 BAP maintained in the dark for elongation. No efficient protocol for root formation was obtained.